Synergy Between Motivation, Innovation, and Facilities in Improving Educational Outcomes: An Analysis of a Study at MA Annur 3 Bululawang - Rahayu, Anggun Septi; Nida; Dianti, Saktia Utami Ayu; Tukan, Virgilia Margaretha Nebo; Sari, Murni Sapta (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2024)
This study is motivated by the importance of motivation, innovation, and learning facilities in supporting the educational process in schools. The study aims to identify issues related to motivation, innovation, and learning facilities in schools. Its primary focus is to determine the extent to which learning motivation, innovative practices, and school facilities impact the quality of education, particularly at MA Annur 3 Bululawang. The research employs a qualitative method with instruments including interviews, observation sheets, and documentation. The subjects of the study are male students of grade XI at MA Annur 3 Bululawang. The results show that, based on interviews with the biology teacher, students' learning motivation is still relatively low, the learning facilities at the school are incomplete, and innovation in the teaching and learning process is lacking. However, different findings were obtained from student questionnaires and observation sheets, which revealed that students' learning motivation reached 72%, scientific facilities scored 82%, and learning innovation scored 67.6%, all categorized as fairly good. This study highlights the need for synergy between teachers, students, and school management to enhance motivation, availability of facilities, and learning innovation for improved educational quality. It is hoped that this research will encourage more interactive and participatory learning by employing methods that actively engage students, such as project-based learning, group discussions, and simulations.